Gender differences in the prevalence of hypertension in a representative sample of Iranian population: the Isfahan Healthy Heart Program - Shirani, S.; Gharipour, M.; Khosravi, et al., A. (Acta Biomedica Atenei Parmensis, 2012)
Background: Management and control of hypertension is an important potential health challenge that may result in considerable cardiovascular adverse events especially for women. In this population-based survey, we sought to determine the epidemiology of hypertension among women compared with men in a community sample of Iranians in the 2008s. Methods: Data were originated from the Isfahan healthy heart program (IHHP) that was designed and launched in 2000 in order to assess the efficacy of lifestyle interventions such as determining the cumulative prevalence of hypertension in a representative sample of Iranian women and to compare it to men. Blood pressure was measured in 12514 individuals (6123 men and 6391 women aged ≥ 19 years) selected through multistage random cluster sampling in each sex and age groups. Baseline data were also collected using a special questionnaire and interviews by expert and trained nurses for this survey. Results: It was revealed a significant increasing trend in the prevalence of hypertension in both urban and rural population in the two genders (p for trend <0.001). The prevalence of hypertension in women was estimated from 4.4 % in subjects aged < 30 years to 39.1% in the elderly aged ≥ 60 years in urban population. Moreover, hypertension was also estimated from 8.6% in individuals aged < 30 years to 32.0% in the elderly aged ≥ 60 years in rural population. Both systolic and diastolic blood pressures were frequently higher in women than in men aged 50-60 years. Women more than men are aware of their blood pressure changes and hypertension is more controlled and under pharmacological treatment in women. Conclusion: Our study supports the pivotal role of women-specific control and management of hypertension and emphasizes the global education programs about the importance of hypertension control and monitoring and also lifestyle modification for reducing the risk of hypertension in Iranian women.